1992
DOI: 10.1071/bt9920599
|View full text |Cite
|
Sign up to set email alerts
|

Seed and Seedling Biology in Relation to Modelling Vegetation Dynamics Under Global Climate Change

Abstract: The distribution of many plant species will change with global climate change, depending on their ability to disperse into, and establish in, new communities. Past migrations of species under climate change have been an order of magnitude slower than the rate of predicted climate change for the next century. The limited evidence available suggests that chance long distance dispersal events will be critically important in determining migration rates. The JABOWA-derived gap replacement models and vital attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The Gaussian model approaches zero rapidly with distance, making migration a coherent, stepwise process, paced by the dispersal parameter ␣ and the rate of population increase. The shapes of these kernels suggest that predicting responses to future climate change (e.g., Leishman et al 1992, Pitelka et al 1997, Clark et al 1998a) will depend on understanding the processes that govern the tail of the dispersal kernels, i.e., the tails of the ␣ distributions in Fig. Clark et al (1998a) suggested that fattailed dispersal kernels might explain the high rates of spread of tree populations at the end of the Pleistocene (Ͼ10 3 m/yr), an explanation consistent with speculations of previous authors (Davis 1987).…”
Section: Implications For Population Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gaussian model approaches zero rapidly with distance, making migration a coherent, stepwise process, paced by the dispersal parameter ␣ and the rate of population increase. The shapes of these kernels suggest that predicting responses to future climate change (e.g., Leishman et al 1992, Pitelka et al 1997, Clark et al 1998a) will depend on understanding the processes that govern the tail of the dispersal kernels, i.e., the tails of the ␣ distributions in Fig. Clark et al (1998a) suggested that fattailed dispersal kernels might explain the high rates of spread of tree populations at the end of the Pleistocene (Ͼ10 3 m/yr), an explanation consistent with speculations of previous authors (Davis 1987).…”
Section: Implications For Population Spreadmentioning
confidence: 99%
“…The shapes of seed shadows assumed by dispersal biologists, modelers, and theorists reflect focus on a particular scale. The restricted dispersal described by such kernels predicts species compositions that can contrast with those from models that assume global dispersal (Leishman et al 1992, Hurtt and Pacala 1993, Ribbens et al 1994, Clark and Ji 1995. 1a), because this shape describes the influence of the nearby (and sometimes overhanging) canopy (Green 1983, Geritz et al 1984, Ribbens et al 1994, Clark et al 1998b.…”
Section: Introductionmentioning
confidence: 99%
“…For example, facilitation alters the spatial pattern of recruitment from that determined by germination (Batllori et al , 2009) but its role in seedling establishment varies geographically for some species (Castro et al , 2004). Information on regeneration under climate change is urgently needed for modelling vegetation dynamics (Leishman et al , 1992; Ibáñez et al , 2007; Morin & Thuiller, 2009; De Frenne et al , 2010). However, the overall impact of climate change on plant regeneration has largely been neglected (Hedhly et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystems should respond through changes in the species composition and productivity of their constituent plant communities (IPCC 1996). As global warming proceeds, vegetation types and zones may shift upward in elevation and latitude (Leishman et al 1992, Grabherr et al 1994, Parmesan 1996, changing plant community composition at each point in space.…”
Section: Introductionmentioning
confidence: 99%